About the recently discovered settlement in the Khurkh river valley (Studia Archaeologica, 2025)
In recent years, satellite remote sensing technology has been increasingly used for archaeological research to locate and study immovable historical and cultural monuments. In 2022, a researcher from the National Museum of Mongolia discovered the ruins of this ancient city through satellite imagery exploration. A preliminary study was conducted in 2023, and in 2025, further research and precise measurements of the site were carried out by joint researchers within the framework of the MON-SOL project. Regarding the function and purpose of the fortified settlements, previous studies have referred to Xiongnu-period settlements located in the valleys of the Kherlen, Tuul, Selenge, Orkhon, and Tamir rivers. The newly identified settlement along the Khurkh River now provides valuable data for understanding the satellite location of Xiongnu fortified settlements. Notably, near this settlement are two significant groups of Xiongnu aristocratic burials in the Duurlig Nars and Bor Bulag complexes. The settlement lies in the ancient valley known as Khurkhonag Jubur (this place noted in the Secret History of the Mongols) near the confluence of the Khurkh and Onon rivers, an area which encompasses archaeological remains from multiple historical periods. This region also represents one of the main concentrations of Xiongnu burials, underscoring its importance. Future studies aim to conduct a detailed research study of the rectangular structure irrigation channels surrounding this settlement to clarify its function.Хурхын хөндийд шинээр илрүүлсэн нэгэн хэрмийн тухайХураангуй. Сүүлийн жилүүдэд сансрын хиймэл дагуулын тусламжтайгаар түүх, соёлын үл хөдлөх дурсгалыг зайнаас тандан судлах, тухайн биетийн байршлыг олж тогтоох зэрэг хайгуулын шинэ арга зүй археологийн шинжлэх ухаанд нэвтэрч байгаа билээ. Энэхүү хэрмийг 2022 онд шинээр сансрын зургийн хайгуулаар Монголын Үндэсний музейн археологич1 илрүүлэн олж, 2023 онд тандалт судалгаа, 2025 онд Мон-Сол төслийн хүрээнд судлаачид хамтран хэмжилтийг хийсэн байна. Уг хэрмийн үүрэг зориулалтыг Хэрлэн, Туул, Сэлэнгэ, Орхон, Тамир голын хөндийд орших Хүннүгийн хот суурины судалгаатай харьцуулсан ба энэ удаад Хурхын хөндийн хэрмийг илрүүлсэн нь Хүннүгийн хэрэмт хотуудын байршил, тархцын судалгаанд чухал хэрэглэгдэхүүн болж байна. Учир нь энэхүү хэрмийн тууриас холгүй Дуурлиг нарс, Бор булгийн хүннүгийн язгууртны бүлэг дурсгал тус тус нэг бүсэд байгаа нь судлаачдын анхаарлыг зүй ёсоор татаж байна. Тиймээс энэхүү дурсгалын онцлог хэв шинжийг дахин нягтлахаар төлөвлөөд байна.Түлхүүр үг: Хэнтий нуруу, гурван баян, хурх гол, хүннү, хэрэм